Artificial Spawning Behavior and Development of Eggs, Larvae and Juveniles of the Red Spotted Grouper, Epinephelus akaara in Korea - Park, Jong Youn (Dev Reprod, 2016)
This study was conducted in order to examine the egg development in red spotted grouper, Epinephelus akaaraand the morphological development of its larvae and juveniles, and to obtain data for taxonomic research. This study was conducted in June 2013, and 50 male and female fish were used for the study. One hundred μg/kg of LHRHa was injected into the body of the fish for inducing spawning, and the fish were kept in a small-sized fish holder (2×2×2 m). Eggs were colorless transparent free pelagic eggs, 0.71–0.77 mm large (mean 0.74±0.02 mm, n=30), and had an oil globule. Hatching started within 27 h after fertilization. Pre-larvae that emerged just after hatching were 2.02–2.17 mm in total length (mean 2.10±0.11 mm), their mouth and anus were not opened yet, and the whole body was covered with a membrane fin. Post-larvae that emerged 15 days post hatching were 3.88–4.07 mm in total length (mean 3.98±0.13 mm), and had a ventral fin with two rays and a caudal fin with eight rays. Juveniles that were formed at 55 d post hatching, were 31.9–35.2 mm in total length (mean 33.6±2.33 mm), with red color deposited over the entire body, and black chromophores deposited in a spotted pattern. The number of fin rays, body color, and shape were the same as that in the adult fish.